Clay-supported copper nitrate (Claycop): a mild reagent for the selective nitration of aromatic olefins - Begari, Eeshwaraiah; Singh, Chandani; Nookaraju, U.; Kumar, Pradeep (Synlett, 2014)
A straightforward and highly selective method has been developed for the nitration of a wide variety of aromatic and aliphatic olefins by using a clay-supported copper nitrate (Claycop) and a catalytic amount of (2,2,6,6-tetramethylpiperidin-1-yl)oxyl, an inexpensive and mild reagent system. High conversions and exclusive E-selectivity, together with the environmentally benign nature of the Claycop reagent, make this a green method and an attractive alternative to established methods.
Keywords: alkenes; nitrations

CeCl3 center dot 7H(2)O-NaI promoted regioselective sulfenylation of indoles with sulfonylhydrazides - Nookaraju, U.; Begari, Eeshwaraiah; Yetra, Ravikiran Reddy; Kumar, Pradeep (Chemistryselect, 2016)
A simple and highly efficient method has been developed for the regioselective sulfenylation of a wide variety of indoles with alkyl and aryl sulfonylhydrazides as a sulphur source and CeCl3 center dot 7H(2)O-Nal as an inexpensive and readily available reagent system. This method involves the breaking of sulfur-oxygen and sulfur-nitrogen bonds and making of carbon-sulfur bond. The method provides high yields of the products with enhanced regioselectivity. We studied the reactivity of various electron rich and electron deficient indoles towards the sulfe-nylation reaction. The indoles containing electron donating group reacts fast towards the sulfenylation reaction as compared to the indoles containing electron withdrawing groups. More over functional groups like alkoxy, aryloxy, bromo, nitro, cyano, ester, were well tolerated under the established reaction conditions. We also proposed a plausible mechanism for this transformation. The experimental simplicity and environmentally benign nature of the reagent system makes this method an attractive alternative to established methods.

Unravelling the nucleophilicity of buten tides for 1,6-conjugate addition to p-quinone methides: a direct access to diversely substituted butenolide-derived diarylmethanes - Sharma, Brijesh M.; Shinde, Dinesh R.; Jain, Ruchi; Begari, Eeshwaraiah; Satbhaiya, Shruti; Gonnade, Rajesh G.; Kumar, Pradeep (Organic Letters, 2018)
A Lewis acid catalyzed regioselective C-C bond is constructed through beta-addition of deconjugated butenolides with p-quinone methides in a 1,6-conjugate addition manner. Interestingly, Lewis acid catalyzed vinylogous Mukaiyama-Michael reaction of silyloxyfurans with p-QMs proceeds selectively through the alpha or gamma position exclusively. The reaction is mild with broad substrate scope, thus allowing easy access to a wide range of bis-arylated alpha-/beta-/gamma-substituted butenolides.

One-pot synthesis of pyrazoles from sulfonyl hydrazides and alkynyl ketones using environmentally benign sulfonium iodate (I) reagent - Mishra, Akanksha; Talukdar, Mrinal; Krishna, Gamidi Rama; Begari, Eeshwaraiah (ChemistrySelect, 2024)
Pyrazole is an omnipresent moiety in many natural products and pharmaceutically active compounds. Here, we have developed a simple and dynamic method for one-pot synthesis of substituted pyrazoles through the intramolecular cyclization of hydrazides and alkynyl ketones, using a novel sulfonium saltbased iodate (& Iukcy;) reagent system. This method has the advantage that it proceeds in a one-pot, without isolating a less stable hydrazone intermediate. Hypervalent iodine-based reagents are an environmentally benign and greener option to toxic metal oxidants; they have an extensive application in metal-catalyst-free reactions, and this reaction proceeds in less time with high yields.
Keywords: Deprotonation; One-pot reaction; Oxidative iodination; Pyrazole; S(N)2-type cyclization